The Effect of Different Natural Extenders in Maintaining the Quality of Sperm Fish (Cyprinus carpio) - Faqih, Abd Raheem; Supriatin, Febriyani Eka; Rahmawati, Aulia; Anitasari, Septi; Maulana, Gilang Drajat; Alim, Muhammad Bachrun (Journal of Aquaculture and Fish Health, 2024)
High demand on   as consume fish nor as decorative fish, causes an increasing production. But, an obstacle occurs on production, due to reproductive characteristic of Common Carp fish. Different time on sperm and eggs production from male and female fish cause difficulties in breeding. Hence, it needed sperm preservation so the breeding could be done in whole year. Natural extenders are the solution to preserve fish sperm without side effect. The purpose of this study was to determine the effect of different types of extenders and different doses on the percentage of sperm motility and viability of carp (Cyprinus carpio) after storage This research was conducted at the Faculty of Fisheries and Marine Sciences, Universitas Brawijaya and the Freshwater Cultivation Installation (IBAT Punten), Batu, East Java. The method in this study was Complete Random Design (CRD) with 6 treatments, K (100ml lactate ringer); A (1ml cider + 99ml lactate ringer); B (1ml coconut + 99ml lactate ringer); C (1ml date juice + 99ml lactate ringer); D (1ml honey + 99ml lactate ringer); E (1ml sugar cane + 99ml lactate ringer). The results showed that the highest motility was obtained in the treatment of using date extract extender with a motility percentage rate of 77.66%; highest viability was obtained in the honey extract with 80.71%; and the highest fertility rate was obtained in the honey extract treatment with 72.67 %.